Gender and Oracular Practice in Deir el-Medîna - Sweeney, Deborah (Zeitschrift für ägyptische Sprache und Altertumskunde, 2008)
Both men and women consulted the oracle of Amenhotep I in Deir el-Medîna, but women seldom appear in texts and images generated by oracular consultations. Most texts mentioning women refer to property matters; the same is true for men, but issues relating to the men′s professional lives, such as wages and appointments, are not mentioned in connection with women. O Berlin P 10629, where a woman consults the oracle in a property dispute with her family, is a particularly intriguing text. If the goods the plaintiff′s mother took away from her are family property, the petitioner is asking the oracle to confirm her future inheritance rights and establish the value of the objects. However, the family quarrel may be about whether the mother is making a false claim to the daughter′s personal property, in which case the oracle is asked to establish the truth.